Interaction of Diversity: An Analysis of the Understanding, Needs, and Challenges of Religious Values in a Multicultural Society - Hyangsewu, Pandu; Abdillah, Hilman Taufik; Rahmania, Puput; Hayatunnisa, Hayatunnisa; Sudaryat, Muhamad Ridwan (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2025)
The motto "Bhinneka Tunggal Ika" (Unity in Diversity) is a hallmark of Indonesia. With this motto, the Indonesian people uphold unity amidst abundant diversity. Unfortunately, in social reality, conflicts stemming from differences in identity often occur. This situation is further complicated in social spaces such as campuses, which are miniature versions of multicultural societies. Therefore, efforts to explore the reality of diverse interactions must be continuously undertaken to find the root of the problem and provide appropriate solutions. This study analyzes the understanding, needs, and challenges of implementing religious values in diverse interactions on campus. Quantitative and qualitative approaches with exploratory descriptive methods were used in this study. The results show that respondents have an inclusive understanding of religious values and require safe spaces for dialogue, early diversity education, and digital religious literacy to support their implementation. Challenges they face include prejudice, fear of being misunderstood, and a lack of interfaith understanding, which undermines inclusive communication in a pluralistic society.